INTEGRATION OF COMPUTER-SUPPORTED COLLABORATIVE LEARNING IN ONLINE MEDICAL SKILLS TRAINING: PERSPECTIVES FROM WOMEN'S ONLINE UNIVERSITY - Nargis Hakimi; Tamanna Quraishi, Musawer Hakimi, Fazila Akrami, Mursal Akrami, Khatera Akrami, Asemah Hasab, FarhDi (International Journal of Teaching and Learning, 2024)
This study investigates the effectiveness of integrating Computer-Supported Collaborative Learning (CSCL) in online medical training, particularly within the context of a women's university. The research addresses a notable gap in the literature by examining the impact of CSCL on student engagement, faculty perceptions, and learning outcomes in medical education settings. The objective is to assess the integration process, evaluate engagement levels, and analyze the effects of CSCL on clinical competency development among female medical students. A quasi-experimental design was employed, involving 133 participants from various departments at the university, including students aged 18-25 and teachers aged 25-35. Data collection was primarily conducted through online questionnaires, focusing on perceptions of CSCL tools, clarity of instructions, engagement levels, and confidence in utilizing CSCL tools. Quantitative data analysis, utilizing SPSS 26, included descriptive statistics, correlation analysis, t- tests, ANOVA, regression analysis, and factor analysis. Key findings reveal positive perceptions of CSCL tools, particularly virtual reality simulations and online quizzes, among participants. There is a significant correlation between the efficacy ratings of CSCL tools and collaboration outcomes, indicating the effectiveness of CSCL in promoting interaction and collaboration among students. Regression analysis identifies predictors of faculty confidence in utilizing CSCL tools, including prior training, years of experience, and frequency of tool usage. The study concludes by highlighting the implications of the findings for medical education and recommending strategies for optimizing CSCL integration in online medical training. The research contributes to enhancing understanding of the role of CSCL in medical education, providing actionable insights for educators, policymakers, and institutions.